Colitis induced by dextran sulphate sodium causes histopathological and immunological changes in the periodontal tissues of Wistar rats - de Mello-Neto, João Martins; Elangovan, Gayathiri; Ervolino, Edilson [UNESP]; Johnson, Newell Walter; Gustafsson, Anders; da Figueredo, Carlos Marcelo (Wiley, 2022)
Objective: This study investigated the impact of colitis induced by dextran sulphate sodium (DSS)-induced colitis (DIC) on histopathological and immunological outcomes in the periodontal tissues of Wistar rats. Background: Inflammatory bowel diseases (IBD) and periodontitis have been reported to present a bidirectional relationship. However, the inflammatory pathway that connects both diseases needs further investigation. Material and Methods: Twenty-five male Wistar rats were allocated in four groups: unilateral ligature-induced periodontitis for 14 days: LIP (n = 7); dextran sulphate sodium-induced colitis only: DIC (n = 6); DIC + LIP (n = 6) and controls (n = 6). Digital images were obtained from the histological sections. In order to assess the attachment loss (AL), the linear distance between the cementoenamel junction (CEJ) and the alveolar bone crest was measured on the mesial root using histological photomicrography's ImageJ software. Immunological analyses of gingival tissues and plasma were performed by Bio-Plex Th1/Th2 Assay. Results: The DIC group showed inflammatory cells extending to the periodontal connective tissues, which contained significantly elevated expressions of IL-1α, IL-1β, IL-2, IL-6, IL-12, IL-13, GM-CSF, IFN-γ and TNF-α compared to controls. There was no significant difference in bone loss between controls and DIC. There were no significant histopathological differences between DIC + LIP and LIP. However, DIC + LIP presented a significantly lower IL-2 and IL-5 than the LIP group. There was no bone loss difference between LIP+DIC and LIP groups. DIC + LIP group presented significantly higher levels of GM-CSF in plasma. Conclusion: DSS-induced colitis was associated with an overexpression of Th1/Th2- related cytokines in the gingival tissue.
Keywords: cytokines; dextran sulphate sodium; gingiva; inflammatory bowel diseases; periodontitis; rats